2020
DOI: 10.1108/sampj-10-2019-0375
|View full text |Cite
|
Sign up to set email alerts
|

The impact of eco-innovation on the stock returns of technology-based KIBS: role of eco-innovation type and its degree of novelty

Abstract: Purpose The purpose of this paper is to determine the role of eco-innovation type and its degree of novelty in increasing the stock returns of technology-based knowledge-intensive business service companies (T-KIBS), to advance the development of the concept of eco-innovation within the literature on the effects of innovation. Design/methodology/approach The effects of four eco-innovation types were examined across three degrees of novelty involved. The event study methodology was applied to the sample of 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Consequently, corporations are now under pressure to recognize climate change as a material business risk and devise policies and procedures accordingly. Against this backdrop, prior literature echoes environment‐focused innovation (also called eco‐innovation) 1 as an effective business strategy for corporations to reduce their environmental footprints (Zaman et al, 2022), gain a competitive advantage (Nadeem et al, 2021), and improve their long‐term financial performance (Szutowski, 2020) and public credibility.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, corporations are now under pressure to recognize climate change as a material business risk and devise policies and procedures accordingly. Against this backdrop, prior literature echoes environment‐focused innovation (also called eco‐innovation) 1 as an effective business strategy for corporations to reduce their environmental footprints (Zaman et al, 2022), gain a competitive advantage (Nadeem et al, 2021), and improve their long‐term financial performance (Szutowski, 2020) and public credibility.…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing the latest research related to this paper, we found that, on the one hand, empirical research using firm data from developed countries mostly concluded that green innovation can improve enterprises' market performance, such as raising the firm value (Farza et al, 2021), reducing the risk of stock price crash (Zaman et al, 2021) and bringing about excess returns to investors (Szutowski, 2021). On the other hand, findings based on emerging economies differ markedly from the foregoing.…”
Section: Introductionmentioning
confidence: 83%
“…In this study, green innovation is conceptualized considering three types widely used in the extant literature: green products, green processes, and green management innovations [38][39][40][41][42][43][44][45][46].…”
Section: Green Innovationmentioning
confidence: 99%
“…This entails enhancing the product's design and features to reduce negative environmental effects [50]. In relation to drivers of GPRD, research indicates that the main drivers include environmental management systems, regulations, cost savings, and market pull factors [45,51]. If consumers' awareness of environmental products is increased via eco-labels, the potential growth in demand will motivate GPRD [46].…”
Section: Green Product Innovation (Gprd)mentioning
confidence: 99%